Cytoreductive surgery followed by chemotherapy and olaparib maintenance in BRCA 1/2 mutated recurrent ovarian cancer: a retrospective MITO group study. Issue 7 (July 2021) - Cecere, Sabrina Chiara; Musacchio, Lucia; Bartoletti, Michele; Salutari, Vanda; Arenare, Laura; Lorusso, Domenica; Ronzino, Graziana; Lauria, Rossella; Cormio, Gennaro; Naglieri, Emanuele; Scollo, Paolo; Marchetti, Claudia; et al.
ABSTRACT : Introduction : The role of cytoreductive surgery in the poly‐ADP ribose polymerase inhibitors era is not fully investigated. We evaluated the impact of surgery performed prior to platinum‐based chemotherapy followed by olaparib maintenance in platinum‐sensitive BRCA‐mutated recurrent ovarian cancer. Methods : This retrospective study included platinum‐sensitive recurrent ovarian cancer BRCA‐mutated patients from 13 Multicenter Italian Trials in Ovarian cancer and gynecological malignancies centers treated between September 2015 and May 2019. The primary outcomes were progression‐free survival and overall survival. Data on post‐progression treatment was also assessed. Results : Among 209 patients, 72 patients (34.5%) underwent cytoreductive surgery followed by platinum‐based chemotherapy and olaparib maintenance, while 137 patients (65.5%) underwent chemotherapy treatment alone. After a median follow‐up of 37.3 months (95% CI: 33.4 to 40.8), median progression‐free survival in the surgery group was not reached, compared with 11 months in patients receiving chemotherapy alone (P<0.001). Median overall survival was nearly double in patients undergoing surgery before chemotherapy (55 vs 28 months, P<0.001). Post‐progression therapy was assessed in 127 patients: response rate to chemotherapy was 29.2%, 8.8%, and 9.0% in patients with platinum‐free interval >12 months, between 6 and 12 months, and <6 months, respectively. Conclusion : Cytoreductive surgery performed before platinum therapy and olaparib maintenance was associated with longer progression‐free survival and overall survival in BRCA‐mutated platinum‐sensitive relapsed ovarian cancer patients. In accordance with our preliminary results, the response rate to chemotherapy given after progression during olaparib was associated with platinum‐free interval.